Predation Time for Halfmoon and Multicolor Plakat of Varieties of Betta Fish Against Aedes aegypti Larvae in Different Water Volume - Adrianto, Hebert; Ritunga, Imelda; Tabita Hasianna Silitonga, Hanna; Ibrahim, Syahriar Nur Maulana Malik (Indonesian Journal of Tropical and Infectious Disease, 2024)
One biological strategy for controlling mosquito vectors is using larvivorous fish as larvae predators. Larvivorous fish are an alternative to overcome the problem of larval resistance to temephos.  Among the many varieties of Betta fish, the specific predation rates associated with each variety and their behavior in different water volumes remain unclear. This study aims to analyze the differences in predation time for halfmoon and a  multicolor plakatof varieties of Betta fish against Aedes aegypti larvae in different water volumes.. The research was conducted as a laboratory experiment using a post-test-only design with five replications. Four treatment groups were established, each consisting of one aquarium filled with a specific water volume, one fish, and 25 Ae. aegypti larvae. The tests began at 12:00 WIB, and the predation time was recorded until all larvae were consumed. The findings showed that all All varieties of Betta fish can typically predate Ae. aegypti larvae. Halfmoon and multicolor plakat have the same predation ability against Ae. aegypti larvae (p > 0.05). The Mann Whitney's results indicated that Betta fish placed in water with a water volume of 1 and 3 liters had no significantly different predation against Ae. aegypti larvae (p > 0.05). However, the Kruskall-Wallis test results showed a significant difference in predation abilities between the two varieties when exposed to different water volumes (p < 0.05) . The multicolor plakat variety displayed the fastest predation time in 1 liter of water, whereas the halfmoon variety predated more quickly in 3 liters of water.